Supporting return to work through appropriate certification: A systematic approach for Australian primary care - Papagoras, H.; Pizzari, T.; Coburn, P.; Sleigh, K.; Briggs, Andrew (CSIRO Publishing, 2017)
Primary care practitioners play a critical role in supporting return to work (RTW) and minimising the detrimental physical and psychosocial sequelae of unnecessary and prolonged work absence in injured and ill workers. Accurate and consistent certification of capacity is an essential component of this role that has been scrutinised recently given the identified variation in certification practices between and within professions. This Perspective outlines the importance of correct certification of capacity for injured workers and provides a RTW flowchart to support systematised and appropriate certification. The flowchart is aimed at primary care practitioners (e.g. general practitioners or physiotherapists). The flowchart was developed at the Transport Accident Commission and WorkSafe Victoria as a guide for Australian primary care practitioners when certifying capacity. A more systematised approach to certification coupled with professional education and support may reduce variations and inaccuracies in certification, improve RTW rates and reduce the increasing burden of disease related to workplace injuries.